Bring your human to work : 10 sure-fire ways to design a workplace that is good for people, great for business, and just might change the world - Keswin, Erica (McGraw-Hill Education, 2019)
Featuring case studies from top brands such as Lyft, Starbucks, Mogul, and SoulCycle, to name a few, this book distills the key practices of the most human companies into applicable advice that any business leader can use to build a human workplace. --